Returning aggregate results of clinical trials: Empirical data of patient preferences. Issue 6 (14th May 2019) - Aldinger, Carmen E.; Ligibel, Jennifer; Shin, Im Hee; Denninger, John W.; Bierer, Barbara E.
Abstract: Introduction: The purpose of this research was to understand the preferences of patients receiving integrative medicine services for return of aggregate study results. Methods: A brief online survey (survey 1) was sent to 341 cancer patients receiving integrative medicine interventions; subsequently, a minimally revised survey (survey 2) was sent to 812 individuals with various medical conditions who had been either research participants in integrative medicine studies ( n = 446) or patients ( n = 346) of mind–body medicine. Results: Feedback to a model plain language summary was elicited from survey 1 and survey 2 respondents. Seventy-seven survey recipients (23%) responded to survey 1, and 134 survey recipients (17%) responded to survey 2. The majority of respondents to the surveys were female and 51–70 years of age. Ninety percent of responders to survey 1 and 89% of responders to survey 2 indicated that researchers should share overall results of a study with participants. In terms of the means of result distribution, 37%–47% preferred email, while 22%–27% indicated that, as long as the results are shared, it did not matter how this occurred. Of 38 survey 1 respondents who had previously participated in a clinical trial, 37% had received the results of their study. In survey 2, 63 individuals indicated that they previously participated in clinical trials, but only 16% recalled receiving results. Conclusions: These results confirm that the majority (89%–90%) of integrative medicine patients are interested in receiving the results of clinical trials. The majority (82%–94%) of respondents felt the model plain language summary of results provided was helpful.